Stories with Pictograms in the Comprehension of Texts of the Initial Level of an Educational Institution - Chavinillo (Docentes 2.0 Journal, 2024)
Nowadays, the concern to develop the understanding of texts starting from childhood leads to mentioning multimodal models to achieve it. Text comprehension is necessary for students; the fundamental value is understanding the content. The present investigation began with the formulation of the general objective, which was to determine the influence between stories with pictograms on the comprehension of texts in 5-year-old students of the initial level of an educational institution - Chavinillo. The following methodologies were applied: hypothetical-deductive method, positivist paradigm, quantitative approach, experimental, explanatory, and longitudinal design. The population is made up of 15 students; the sample is made up of all students. Regarding the technique, the observation guide was used for the two variables, and the instrument used to measure both variables was observation. The main conclusion was that stories with pictograms significantly influence text comprehension, which is demonstrated with the Student T test = -8.367, its significance being 0.000, rejecting the null hypothesis and accepting the alternative hypothesis, using the Student T test and the decision rule, if the p-value is less than 0.005, the alternative hypothesis is accepted.
Keywords: Stories; pictograms; text comprehension; initial level